Synthesis, antibacterial evaluation and in silico studies of novel 2-(benzo[d]thiazol-2-yl)-N-arylacetamides and their derivatives as potential DHFR inhibitors - Nadia Hanafy Metwally; Galal Hamza Elgemeie; Aya Ragab Abdelrazek; Salwa Magdy Eldaly (BMC Chemistry)
Abstract Novel N-arylacetamides 2a–f were synthesized based on benzo[d]thiazole scaffold. The compounds 2a–c underwent Knoevenagel condensation through green synthetic method with different aromatic aldehydes and pyrazole-7-carbaldehydes delivered the respective arylidenes with efficient yields. Arylidenes 4 reacted with malononitrile affording the corresponding N-arylpyridones 11a–i. Moreover, the reaction of 2a–c with each of salicylaldehyde and 5-arylazo salicylaldehydes afforded the unexpected coumarins rather than quinolin-5-ones. The structure of coumarin 8 was confirmed by density functional theory (DFT) calculations using basis set B3LYP/6-311 G +  + (d,p) to obtain the suitable geometrical structure with molecular orbitals` energies revealing its planar structure and its agreement with experimental data. Besides, the antibacterial activity was tested against different bacterial strains revealing potent activity especially Gram-negative bacteria with excellent minimum inhibition concentration (MIC) value ranging from 31.25 to 250 µg/L. Additionally, compounds 2c and 4m showed enzyme inhibition against dihydrofolate reductase in Escherichia coli with greater potency (IC50 for 2c = 3.796 µM, IC50 for 4m = 2.442 µM) than the standard antibiotic trimethoprim (IC50 = 8.706 µM). Investigation of the physicochemical properties of the newly compounds exhibited their better ADME properties that can be developed for the discovery of new antibacterial agents. Graphical Abstract